Big Data of the Past - Kaplan, Frédéric; di Lenardo, Isabella (Frontiers in Digital Humanities, 2017)
Big Data is not a new phenomenon. History is punctuated by regimes of data acceleration, characterized by feelings of information overload, social transformation and invention of new technologies. During these moments, private organizations, administrative powers and sometimes isolated individuals have produced important datasets organized following a - now often superseded but nevertheless - coherent logic. To be translated into relevant sources of information about our past, these document series need to be redocumented using contemporary paradigms. The intellectual, methodological and technological challenges linked with this translation process are the central subject of this article.